Low-smoke halogen-free flame-retardant photovoltaic cable and preparation method thereof

By using modified polyvinyl chloride and magnesium aluminum hydrotalcite in the photovoltaic cable insulation layer, the problem of poor fire-retardant flame retardant performance of the photovoltaic cable insulation layer is solved, and the effect of maintaining excellent flame retardant performance after long-term use is achieved.

CN119775694AActive Publication Date: 2025-04-08MINGPIN CABLE GRP CO LTD

Patent Information

Application Number
CN202510268005.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-07
Publication Date
2025-04-08
Estimated Expiration
2045-03-07

AI Technical Summary

Technical Problem

The fire-retardant and flame-retardant performance of the existing photovoltaic cable insulation layer is not ideal, especially after long-term use, which leads to the inability to effectively guarantee safety.

Method used

Modified polyvinyl chloride, polyethylene, ethylene propylene ternary rubber and additives are used to mix and granulate, and magnesium aluminum hydrotalcite is evenly dispersed on the surface of polyvinyl chloride through the esterification reaction to form a low-smoke, halogen-free flame-retardant photovoltaic cable.

Benefits of technology

It significantly improves the fire-retardant performance of the insulating layer of the photovoltaic cable, ensures that excellent flame-retardant performance can be maintained after long-term use, and enhances the safety of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a low-smoke halogen-free flame-retardant photovoltaic cable and a preparation method thereof, and relates to the technical field of cable processing. The preparation method comprises the following steps: carrying out mixing granulation on modified polyvinyl chloride, polyethylene, ethylene propylene diene monomer and an auxiliary agent to obtain a master batch; melting and extruding the master batch, and coating the surface of the conductor wire core with the master batch to obtain the photovoltaic cable; wherein the surface of the modified polyvinyl chloride is connected with magnesium-aluminum hydrotalcite through esterification reaction. The obtained master batch is melted and extruded on the surface of a conductor wire core to serve as an insulating layer, and due to the fact that modified polyvinyl chloride is better in flame retardance and ageing resistance, the safety of the photovoltaic cable can be improved, and the service life of the photovoltaic cable can be prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cable processing, and in particular to a low-smoke, halogen-free, flame-retardant photovoltaic cable and a preparation method thereof. Background Art

[0002] Photovoltaic cables are special cables in solar power generation systems, mainly used for power transmission between components and between components and inverters. The basic structure of photovoltaic cables includes: conductor core, insulation layer and sheath layer. The conductor is usually made of high-purity oxygen-free copper or tinned copper, the insulation layer is usually made of high molecular polymer, and the sheath layer is made of high molecular or composite materials with heat resistance, UV resistance, acid and alkali resistance, moisture resistance and other characteristics.

[0003] According to the actual use requirements and application scenarios of photovoltaic cables, there are certain differences in the structure of photovoltaic cables, but the insulation layer is always a very important and indispensable structure in photovoltaic cables, which plays the role of protecting the wire core and preventing leakage.

[0004] Since photovoltaic cables are often used in harsh outdoor environments, they must be resistant to high temperatures, UV rays, and corrosion. In addition to meeting the above performance requirements, the fire retardant properties of photovoltaic cables are also crucial.

[0005] As mentioned above, the insulation layer of photovoltaic cables generally uses high molecular compounds such as polyvinyl chloride (PVC), polyethylene (PE), ethylene propylene rubber (EPR) or their combinations. The shortcomings of the related prior art are that the fire retardant performance of the insulation layer material is not ideal.

[0006] Especially for photovoltaic cables, which work in harsh outdoor environments for a long time, the fire retardant performance of the insulation layer will further deteriorate after long-term use and aging, resulting in the safety of photovoltaic cables not being effectively guaranteed. Summary of the invention

[0007] One of the problems solved by the present invention is how to provide a low-smoke, halogen-free, flame-retardant photovoltaic cable with excellent fire-retardant properties, especially after long-term use, the fire-retardant properties can still be effectively guaranteed.

[0008] In order to solve at least one of the above problems, the present invention provides a method for preparing a low-smoke halogen-free flame-retardant photovoltaic cable, comprising: S1, mixing and granulating modified polyvinyl chloride, polyethylene, EPDM rubber and additives to obtain masterbatch; S2, melt-extrude the masterbatch and coat it on the surface of the conductor core to obtain a photovoltaic cable; The surface of the modified polyvinyl chloride is linked with magnesium aluminum hydrotalcite through an esterification reaction.

[0009] In any of the above technical solutions, the additives include stabilizers, plasticizers and antioxidants; in terms of mass ratio, polyvinyl chloride: polyethylene: EPDM rubber: stabilizer: plasticizer: antioxidant = (60-66): (20-22): (8-12): (2-4): (1-2): (1-2).

[0010] In any of the above technical solutions, the stabilizer includes at least one of the following or a combination thereof: trimethyl phosphate, barium stearate, and calcium zinc dimer acid.

[0011] In any of the above technical solutions, the plasticizer includes at least one of the following or a combination thereof: trioctyl trimellitate, tetramethyl phthalate, and dioctyl phthalate.

[0012] In any of the above technical solutions, the antioxidant includes at least one of the following or a combination thereof: pentaerythritol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and dilauryl thiodipropionate.

[0013] In any of the above technical solutions, the mixing temperature of the mixing and granulation is 90° C. to 120° C., the mixing speed is 600 r / min to 1200 r / min, and the mixing time is 15 min to 20 min.

[0014] In any of the above technical solutions, the melting temperature of melt extrusion is 185° C. to 200° C., and the melting time is 20 min to 40 min.

[0015] In any of the above technical solutions, the modified polyvinyl chloride is prepared by the following steps: A1. Treating polyvinyl chloride with glutathione to obtain carboxylated polyvinyl chloride; A2, treating the hydrotalcite with serine to obtain hydroxylated magnesium aluminum hydrotalcite; A3. Mix and heat hydroxylated magnesium aluminum hydrotalcite and carboxylated polyvinyl chloride under acidic conditions to obtain modified polyvinyl chloride.

[0016] In any of the above technical solutions, the hydroxylated magnesium aluminum hydrotalcite is subjected to chemical expansion intercalation treatment using ammonium sulfate and serine as intercalation agents, and ultrasonic expansion intercalation treatment.

[0017] In any of the above technical solutions, the modified polyvinyl chloride is prepared by the following steps: B1. Dissolve glutathione in water, add triethanolamine, polyvinyl alcohol, polyvinyl chloride and ethanol, heat and reflux to obtain carboxylated polyvinyl chloride; B2, after ammonium persulfate, serine, pyrophosphoryl chloride and magnesium aluminum hydrotalcite are uniformly mixed, water is added for chemical expansion and intercalation treatment, and then calcium chloride aqueous solution is added dropwise and alkalization treatment is performed to obtain hydroxylated magnesium aluminum hydrotalcite; B3. Add concentrated sulfuric acid, hydroxylated magnesium aluminum hydrotalcite and carboxylated polyvinyl chloride into ethanol, heat and apply ultrasound to perform ultrasonic expansion and intercalation treatment, and then heat and reflux to react to obtain modified polyvinyl chloride.

[0018] In any of the above technical solutions, in B1, the mass ratio of triethanolamine:polyvinyl alcohol:glutathione:polyvinyl chloride:water:ethanol is (2-4):(4-6):(6-8):(20-30):(10-15):100.

[0019] In any of the above technical solutions, in B2, the mass ratio of calcium chloride: ammonium sulfate: serine: pyrophosphoryl chloride: magnesium aluminum hydrotalcite is (6-10): (4-8): (60-80): (10-20): 100.

[0020] In any of the above technical solutions, in B3, the mass ratio of concentrated sulfuric acid: hydroxylated magnesium aluminum hydrotalcite: carboxylated polyvinyl chloride: ethanol = (15-20): (4-6): 100:300.

[0021] In any of the above technical solutions, in B1, the temperature of the heating reflux reaction is 80° C. to 90° C., and the time is 8 h to 12 h.

[0022] In any of the above technical solutions, in B2, magnesium-aluminum hydrotalcite is prepared by a chemical method in an alkaline environment using magnesium salt and aluminum salt as raw materials.

[0023] In any of the above technical solutions, in B3, the frequency of the ultrasonic expansion treatment is 80 kHz to 120 kHz, and the time is 2 h to 3 h.

[0024] In any of the above technical solutions, in B3, the temperature of the heating reflux reaction is 80° C. to 90° C., and the time is 2 h to 4 h.

[0025] The present invention also provides a low-smoke halogen-free flame-retardant photovoltaic cable, which is obtained by using the preparation method of any of the above technical solutions.

[0026] Beneficial Effects The present invention provides a method for preparing a low-smoke, halogen-free, flame-retardant photovoltaic cable, which comprises firstly mixing and granulating modified polyvinyl chloride, polyethylene, ethylene propylene diene monomer rubber and an additive to obtain a master batch. Then, the master batch is melt-extruded and coated on the surface of a conductor core to obtain a photovoltaic cable. The surface of the modified polyvinyl chloride is connected with magnesium aluminum hydrotalcite through an esterification reaction.

[0027] In the first aspect, the present invention controls the basic components and proportions of the insulating layer materials used in photovoltaic cables. The three main polymer raw materials used in the insulating layer materials are polyvinyl chloride, polyethylene and ethylene propylene diene monomer rubber. As mentioned above, among many polymer materials, polyvinyl chloride has relatively good thermal stability, chemical stability and mechanical strength. Polyethylene and polyvinyl chloride have a certain compatibility during processing. Adding an appropriate amount of polyethylene can improve the processing performance of polyvinyl chloride and improve its fluidity and extrusion efficiency. A small amount of ethylene propylene diene monomer rubber has excellent weather resistance, which helps to keep the performance of the insulating material stable in harsh environments.

[0028] In the second aspect, the present invention improves the preparation process of the insulating layer material used in photovoltaic cables. In the prior art, generally, high molecular polymers such as polyvinyl chloride and polyethylene, and various inorganic or organic additives are mixed, granulated and melt-extruded. For inorganic additives (generally flame retardants or toughening agents), the surface energy thereof is quite different from the surface energy of polymers, which is the reason for the poor dispersion performance of inorganic additives in high molecular polymers. In the prior art, generally, nano-sized inorganic materials are prepared, coupling agent treatment is carried out, surface defects are manufactured, etc., and the surface properties of inorganic additives are changed to promote their dispersion in high molecular polymers. Different from the prior art, the present invention is committed to using magnesium aluminum hydrotalcite as an inorganic additive, and through wet chemical process and organic chemical reaction, hydroxyl and carboxyl groups are respectively aggregated on the surface of magnesium aluminum hydrotalcite and polyvinyl chloride, and then the esterification reaction of hydroxyl and carboxyl groups under specific reaction conditions is used to disperse the magnesium aluminum hydrotalcite powder evenly and firmly on the surface of polyvinyl chloride in a chemically linked manner. The above pre-chemical bonding treatment ensures that the magnesium aluminum hydrotalcite is evenly dispersed in the polyvinyl chloride and is not easy to agglomerate during the subsequent melt mixing. It also makes the insulation material stable in performance and not easy to age during long-term use, and has better flame retardant properties as well as mechanical and mechanical properties, which can be maintained for a long time.

[0029] In the third aspect, in order to chemically link magnesium aluminum hydrotalcite with polyvinyl chloride through esterification reaction, the present invention needs to perform hydroxylation treatment on magnesium aluminum hydrotalcite and perform carboxylation treatment on polyvinyl chloride. Among various treatment agents capable of achieving hydroxylation or carboxylation, the present invention selects glutathione to perform carboxylation treatment on polyvinyl chloride, and selects serine salt to perform hydroxylation treatment on hydrotalcite. Glutathione is formed by peptide bond condensation of three amino acids, glutamic acid, cysteine ​​and glycine, and has two carboxyl groups and one sulfhydryl group. Through nucleophilic substitution reaction between sulfhydryl group and chlorine atom of polyvinyl chloride, the carboxyl group of glutathione is introduced into the macromolecular chain of polyvinyl chloride, thereby obtaining polyvinyl chloride with more carboxyl groups linked thereto. Serine contains amino, hydroxyl and carboxyl groups. Among them, hydroxyl group can be used to chemically link with carboxylated polyvinyl chloride through esterification reaction. Carboxyl group helps serine to enter the interlayer of magnesium aluminum hydrotalcite. In order to combine serine with magnesium-aluminum hydrotalcite, serine needs to be intercalated into the interlayer of magnesium-aluminum hydrotalcite. The van der Waals diameter of serine is relatively large, and the interlayer distance of magnesium-aluminum hydrotalcite and the van der Waals diameter of serine are relatively small. In order to allow more serine to enter the interlayer of magnesium-aluminum hydrotalcite, the interlayer distance of magnesium-aluminum hydrotalcite needs to be further opened. The present invention grinds and mixes ammonium sulfate, serine, pyrophosphoryl chloride and magnesium-aluminum hydrotalcite in acetone, adds a small amount of water and stands for reaction. In this process, ammonium sulfate decomposes and releases gas in an aqueous environment, and the pressure brought by the gas release drives the hydrotalcite to expand uniformly, and the interlayer distance increases. In addition, ammonium sulfate produces hydrogen ions due to the hydrolysis of ammonium ions in water, thereby creating an acidic environment. Under acidic conditions, a proton in the carboxyl group of serine will be transferred to the amino group to form ammonium ions. The further increased number of ammonium ions can exchange more cations between the hydrotalcite interlayers, help open the interlayer distance of the hydrotalcite, and promote the intercalation of serine into the hydrotalcite. In addition, by dripping calcium chloride aqueous solution and creating an alkaline environment, the interlayer cations of the magnesium aluminum hydrotalcite can be subjected to ion exchange reaction with calcium ions, so that calcium ions are introduced into the interlayer. The phosphate ions produced by the hydrolysis of pyrophosphoryl chloride can increase the interlayer distance of the magnesium aluminum hydrotalcite, and can also be combined with calcium ions through electrostatic interaction, effectively adsorbing and capturing calcium ions into the interlayer of the magnesium aluminum hydrotalcite. Therefore, ammonium sulfate, calcium salt and serine are coordinated with each other and treated by chemical intercalation, which helps to make more serine enter the interlayer of the magnesium aluminum hydrotalcite. Thus, the expansion of the interlayer distance and the combination with serine improve the dispersibility of the magnesium aluminum hydrotalcite of the present invention, and are easier to be linked to carboxylated polyvinyl chloride.

[0030] In the fourth aspect, before the esterification reaction, the present invention heats and ultrasonically expands the mixture of hydroxylated magnesium aluminum hydrotalcite and carboxylated polyvinyl chloride, and concentrated sulfuric acid can be used as a catalyst to drive the occurrence of the esterification reaction under heating conditions of 80°C to 90°C, thereby achieving the purpose of linking the magnesium aluminum hydrotalcite on the surface of the modified polyvinyl chloride through the esterification reaction. The above method ensures the uniform dispersion of the magnesium aluminum hydrotalcite and avoids its agglomeration in the melting process. In addition, for polyvinyl chloride materials, they slowly decompose and release hydrogen chloride during long-term use, and hydrogen chloride can capture active free radicals, resulting in the degradation of polyvinyl chloride. The magnesium aluminum hydrotalcite is evenly distributed in the polyvinyl chloride, which helps the magnesium aluminum hydrotalcite to fully capture the hydrogen chloride generated by the degradation of polyvinyl chloride, interrupt the degradation chain reaction, and thus achieve the purpose of stabilizing the polyvinyl chloride and preventing its aging. DETAILED DESCRIPTION

[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, a detailed description is given below in conjunction with specific embodiments of the present invention.

[0032] Unless otherwise specified, the reagents and raw materials used in the present invention can be purchased through commercial channels. The experimental methods in the following examples without specifying specific conditions are selected according to conventional methods and conditions, or according to the product specifications.

[0033] The present invention provides a method for preparing a low-smoke, halogen-free, flame-retardant photovoltaic cable, which at least comprises a core and an insulating layer. For photovoltaic cables, the core is generally made of high-purity oxygen-free copper or tinned copper, and the insulating layer is generally made of high molecular compounds such as polyvinyl chloride, polyethylene, ethylene-propylene rubber, or a combination thereof.

[0034] As an insulating material, polyvinyl chloride is widely used in the wire and cable industry because, in addition to having sufficient electrical insulation properties, polyvinyl chloride also has high strength and hardness, and can withstand certain mechanical stress, thereby achieving the purpose of protecting the cable core.

[0035] One of the important criteria for measuring the performance of polyvinyl chloride insulation materials is flame retardancy. In order to improve the fire and heat resistance of such insulation materials, flame retardants can be added to them. Flame retardants generally include inorganic flame retardants and organic flame retardants. Inorganic flame retardants mainly include inorganic compounds such as magnesium hydroxide, aluminum hydroxide, montmorillonite, diatomaceous earth, etc. Organic flame retardants mainly include halogen flame retardants (such as decabromodiphenyl ether, tetrabromobisphenol A, hexabromocyclododecane, etc.), phosphorus flame retardants (such as phosphate esters, phosphaphenanthrene, phosphazene compounds, etc.), nitrogen flame retardants (such as melamine, melamine cyanurate), etc.

[0036] Some flame retardant materials release smoke when burning. Since its diffusion speed is much faster than the flame diffusion speed, it can easily hinder the rapid evacuation of personnel and fire fighting. Therefore, some inorganic flame retardants with smoke-free and smoke-suppressing effects have gradually become the focus and hot spot of research by technical personnel in this field.

[0037] Among various inorganic flame retardants, magnesium aluminum hydrotalcite is a more commonly used and effective one. Magnesium aluminum hydrotalcite belongs to layered double hydroxides (LDH), which is a compound with a special layered structure. Magnesium aluminum hydrotalcite has the advantages of both magnesium hydroxide and aluminum hydroxide flame retardants. It absorbs a lot of heat and releases a lot of water and carbon dioxide through decomposition at high temperature, and has excellent flame retardancy and smoke suppression. In addition, the magnesium aluminum oxide generated after the decomposition of hydrotalcite combines with the carbonized product formed when the polymer material is burned to form a protective film on the surface of the material, blocking the intrusion of oxygen, thereby enhancing the flame retardant effect.

[0038] Despite the above advantages, magnesium aluminum hydrotalcite also has certain shortcomings when used as a flame retardant for polyvinyl chloride materials.

[0039] Since hydrotalcite particles are easily unevenly dispersed in the polymer matrix, hydrotalcite will agglomerate in materials such as polyvinyl chloride and polyethylene, which not only makes it difficult to fully exert its flame retardant effect, but may also reduce the mechanical and mechanical properties (such as tensile strength, etc.) of the polymer material and accelerate the aging rate during long-term use. Therefore, if the uniformity of the dispersion of magnesium-aluminum hydrotalcite in polyvinyl chloride materials can be improved, it will be helpful to improve the mechanical and mechanical properties and flame retardant properties of polyvinyl chloride insulation materials.

[0040] Based on the above reasons, the present invention modifies the prior art through the following technical scheme, in order to improve the flame retardant properties of the photovoltaic cable insulation layer (especially the flame retardant properties after long-term use), and at the same time improve its mechanical and mechanical properties, thereby providing a photovoltaic cable that is more suitable for long-term use in harsh outdoor natural environments.

[0041] The present invention provides a method for preparing a low-smoke halogen-free flame-retardant photovoltaic cable, the method comprising: S1, mixing and granulating modified polyvinyl chloride, polyethylene, EPDM rubber and additives to obtain masterbatch; S2, melt-extrude the masterbatch and coat it on the surface of the conductor core to obtain a photovoltaic cable; The surface of the modified polyvinyl chloride is linked with magnesium aluminum hydrotalcite through an esterification reaction.

[0042] The present invention preferably uses polyvinyl chloride with an average molecular weight of 50000-100000. The additives used in the present invention include stabilizers, plasticizers and antioxidants. Among them, the functions of the above additives belong to the prior art, and the present invention will not repeat them here.

[0043] Regarding the component ratio, preferably, based on the mass ratio, polyvinyl chloride: polyethylene: EPDM rubber: stabilizer: plasticizer: antioxidant = (60-66): (20-22): (8-12): (2-4): (1-2): (1-2).

[0044] It can be understood that the main raw material of the insulating material of the present invention is polyvinyl chloride, and appropriate polyethylene can improve the processing performance of polyvinyl chloride, improve its fluidity and extrusion efficiency, and a small amount of EPDM rubber is used to improve the weather resistance of the insulating material. The above ratio enables the insulating material of the present invention to remain relatively stable under extreme outdoor climate conditions, so it is more suitable for use in photovoltaic cables; and it is easy to process and shape, and has a wide process window requirement for melting and extrusion.

[0045] In the present invention, the modified polyvinyl chloride is prepared by the following steps: A1. Treating polyvinyl chloride with glutathione to obtain carboxylated polyvinyl chloride; A2, treating the hydrotalcite with serine to obtain hydroxylated magnesium aluminum hydrotalcite; A3. Mix and heat hydroxylated magnesium aluminum hydrotalcite and carboxylated polyvinyl chloride under acidic conditions to obtain modified polyvinyl chloride.

[0046] Specifically, in A1, the method of treating polyvinyl chloride with glutathione is: dissolving glutathione in water, adding triethanolamine, polyvinyl alcohol, polyvinyl chloride and ethanol, heating and refluxing reaction, and obtaining carboxylated polyvinyl chloride. After obtaining carboxylated polyvinyl chloride, the solvent can be removed under negative pressure, and the solvent and acid binding agent can be recycled. Preferably, in terms of mass ratio, triethanolamine: polyvinyl alcohol: glutathione: polyvinyl chloride: water: ethanol = (2-4): (4-6): (6-8): (20-30): (10-15): 100. The temperature of the heating reflux reaction is preferably 80°C to 90°C, and the time is 8h to 12h.

[0047] Glutathione is formed by the condensation of three amino acids, glutamic acid, cysteine ​​and glycine, through peptide bonds, and has two carboxyl groups and one thiol group. In the above steps, triethanolamine and polyvinyl alcohol are used as acid-binding agents, and ethanol is mainly used as the reaction medium. By heating and refluxing, the thiol group of glutathione and the chlorine atom of polyvinyl chloride undergo a nucleophilic substitution reaction, thereby introducing the carboxyl group of glutathione into the macromolecular chain of polyvinyl chloride to obtain polyvinyl chloride connected with carboxyl groups.

[0048] In A2, the preparation method of the hydrotalcite is: using magnesium salt and aluminum salt as raw materials, and preparing by chemical method in an alkaline environment. The specific steps are as follows: magnesium chloride and aluminum nitrate are evenly dispersed in water according to the mass ratio of magnesium chloride: aluminum nitrate: water = (10-15): (20-25): 100 to obtain a magnesium aluminum salt solution; 6wt% to 12wt% of an alkali metal hydroxide aqueous solution is added dropwise to the magnesium aluminum salt solution and stirred until the pH value reaches 10 to 12, and after standing and aging for 2h to 4h, the solid is filtered, washed, and dried to obtain magnesium aluminum hydrotalcite; wherein the alkali metal hydroxide aqueous solution is an aqueous solution of sodium hydroxide or potassium hydroxide.

[0049] In A2, the method of treating hydrotalcite with serine is: after ammonium persulfate, serine, pyrophosphoryl chloride, and magnesium aluminum hydrotalcite are uniformly mixed, water is added for chemical expansion and intercalation treatment, and then calcium chloride aqueous solution is added dropwise and alkalization treatment is performed to obtain hydroxylated magnesium aluminum hydrotalcite. Preferably, in terms of mass ratio, calcium chloride: ammonium sulfate: serine: pyrophosphoryl chloride: magnesium aluminum hydrotalcite = (6-10): (4-8): (60-80): (10-20): 100 The purpose of the above steps is to intercalate serine into the interlayer of magnesium aluminum hydrotalcite. Considering that the interlayer spacing of magnesium aluminum hydrotalcite is about 0.77nm, the van der Waals diameter of serine is more than 0.56nm, and the size difference between the two is small, in order to allow more serine to enter the interlayer of magnesium aluminum hydrotalcite, it is necessary to further open the interlayer spacing of magnesium aluminum hydrotalcite. To this end, the present invention mixes ammonium sulfate, serine, pyrophosphoryl chloride and magnesium aluminum hydrotalcite in a certain proportion, grinds and mixes evenly in a sufficient amount of acetone, and then takes out. After taking out, it can be directly added with a small amount of water and allowed to stand for reaction without washing. In this process, ammonium sulfate chemically intercalates magnesium aluminum hydrotalcite, promoting ammonium ions and serine to enter the interlayer of magnesium aluminum hydrotalcite. Serine will also further release intercalated ammonium ions in the acidic environment of ammonium sulfate. The addition of calcium chloride allows ammonium sulfate, calcium salt and serine to cooperate with each other, and through chemical intercalation treatment, calcium ions also help to allow more serine to enter the interlayer of magnesium aluminum hydrotalcite.

[0050] In A3, the hydroxylated magnesium aluminum hydrotalcite and carboxylated polyvinyl chloride are mixed and heated under acidic conditions for esterification reaction in the following manner: concentrated sulfuric acid, hydroxylated magnesium aluminum hydrotalcite, and carboxylated polyvinyl chloride are added to ethanol, heated and ultrasonic waves are applied for ultrasonic expansion and intercalation treatment, and then heated for reflux reaction to obtain modified polyvinyl chloride. Preferably, in terms of mass ratio, concentrated sulfuric acid: hydroxylated magnesium aluminum hydrotalcite: carboxylated polyvinyl chloride: ethanol = (15-20): (4-6): 100: 300. Preferably, the frequency of the ultrasonic expansion treatment is 80kHz to 120kHz, and the time is 2h to 3h. The temperature of the heating reflux reaction is 80°C to 90°C, and the time is 2h to 4h.

[0051] The low temperature heating and ultrasonic expansion before esterification are to further optimize the intercalation effect. The esterification reaction is driven under the heating condition of 80°C to 90°C, so that the purpose of linking the magnesium aluminum hydrotalcite on the surface of the modified polyvinyl chloride through the esterification reaction can be achieved. Preferably, in the esterification reaction, a water-carrying agent can be used for timely dehydration. The water-carrying agent can be a molecular sieve or an organic water-carrying agent such as cyclohexane.

[0052] After obtaining the modified polyvinyl chloride, the granulation and melting processes can be carried out using existing technologies. The specifications of the stabilizer, plasticizer and antioxidant can be selected and adjusted by those skilled in the art. Exemplarily, the stabilizer includes at least one of the following or a combination thereof: trimethyl phosphate, barium stearate, calcium zinc dimer acid. The plasticizer includes at least one of the following or a combination thereof: trioctyl trimellitate, tetramethylbenzene tetradecanoate, dioctyl phthalate. The antioxidant includes at least one of the following or a combination thereof: pentaerythritol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid n-octadecyl alcohol ester, dilauryl thiodipropionate.

[0053] The mixing and granulation of modified polyvinyl chloride, polyethylene, EPDM rubber and additives can be carried out by a mixer and a granulation device, and the size of the granules is preferably 0.5 mm to 2 mm. Melt extrusion is carried out by a melting device and a screw extrusion device, and the temperature range of the melting device and the speed of the screw extrusion device can be selected and adjusted by those skilled in the art.

[0054] Preferably, the mixing temperature of the mixing granulation is 90°C to 120°C, the mixing speed is 600r / min to 1200r / min, and the mixing time is 15min to 20min. The melting temperature of the melt extrusion is 185°C to 200°C, and the melting time is 20min to 40min.

[0055] In the process of melt-extruding and coating the masterbatch on the surface of the conductor core, the conductor core used can be obtained by the following steps: B1. Screening the conductive metal blanks; B2, drawing the screened conductive metal blank into bare wire; B3, twist the bare wires to form a wire core; Among them, the conductive metal blank is preferably industrial pure copper. The screening criteria of B1 are: through image detection combined with manual screening, a conductive metal blank with no surface defects such as oxidation, burrs, cracks, etc. is obtained. The wire drawing step of B2 includes: using a wire drawing machine to grade and stretch the conductive metal blank to a metal wire of a target diameter (preferably 0.1mm to 0.4mm); after the stretching is completed, the metal wire is sent into a steam chamber, and the temperature in the steam chamber is controlled at 78°C to 80°C, and the heat is kept in the steam chamber for 2h to 3h; then an annealing furnace is used to anneal the metal wire at a temperature of 550°C to 650°C for 2h to 4h; finally, oil and dust are cleaned to obtain a bare wire. In B3, the number of bare wires required to be twisted to form a core can be determined by a technician in this field according to actual needs.

[0056] It can be understood that after the insulating material is coated on the surface of the conductor core, a cable coated with an insulating layer is obtained. Those skilled in the art can continue to apply or fill other materials outside the cable according to actual needs. For example, in order to protect the cable, it is necessary to wrap a sheath layer outside the insulating layer. In addition, the photovoltaic cable may also include a shielding layer located between the insulating layer and the sheath layer. The shielding layer is mainly used to reduce electromagnetic interference. The shielding material may be copper wire, aluminum wire, steel wire, etc. The sheath layer may also be filled with a filling layer. The filling layer is mainly used to make the cable round and stabilize the structure. Some fillers also have water-blocking and flame-retardant functions. Commonly used materials include polypropylene rope, glass fiber rope, asbestos rope, etc. In addition, other structures such as an anti-puncture layer, an armor layer, and a waterproof layer may be provided between the insulating layer and the sheath layer. The sheath layer may be one layer or two layers including an inner sheath layer and an outer sheath layer.

[0057] Embodiment 1 In this embodiment, a magnesium aluminum hydrotalcite sample is prepared, and the preparation steps are as follows: 1. Disperse magnesium chloride and aluminum nitrate in distilled water at a mass ratio of magnesium chloride: aluminum nitrate: water = 10:20:100, stir evenly with magnetic force to obtain a magnesium aluminum salt solution; 2. Add 8 wt % sodium hydroxide aqueous solution to the magnesium aluminum salt solution and stir until the pH value reaches 11. After standing for 2 hours, filter the solid, wash once with ethanol, wash twice with water, and dry at 110° C. to obtain magnesium aluminum hydrotalcite sample 1.

[0058] Embodiment 2 In this embodiment, a magnesium aluminum hydrotalcite sample is prepared, and the preparation steps are as follows: 1. Disperse magnesium chloride and aluminum nitrate in distilled water at a mass ratio of magnesium chloride: aluminum nitrate: water = 15:25:100, stir evenly with magnetic force to obtain a magnesium aluminum salt solution; 2. Add 6 wt % sodium hydroxide aqueous solution to the magnesium aluminum salt solution and stir until the pH value reaches 11. After standing for 4 hours, filter the solid, wash once with ethanol, wash twice with water, and dry at 110° C. to obtain magnesium aluminum hydrotalcite sample 2.

[0059] Embodiment 3 This example prepares a carboxylated polyvinyl chloride sample, and the preparation steps are as follows: 1. Dissolve glutathione in water according to the mass ratio of triethanolamine: polyvinyl alcohol: glutathione: polyvinyl chloride: water: ethanol = 2:6:6:20:10:100, then add triethanolamine, polyvinyl alcohol, polyvinyl chloride and ethanol and mix well to obtain a first mixture; 2. The first mixture was heated to reflux at 85° C. for 10 h, the solvent was removed, the reaction product was washed once with ethanol, twice with water, and dried with hot air at 80° C. to obtain carboxylated polyvinyl chloride sample 1.

[0060] Embodiment 4 This example prepares a carboxylated polyvinyl chloride sample, and the preparation steps are as follows: 1. Dissolve glutathione in water according to the mass ratio of triethanolamine: polyvinyl alcohol: glutathione: polyvinyl chloride: water: ethanol = 4:4:8:30:15:100, then add triethanolamine, polyvinyl alcohol, polyvinyl chloride and ethanol and mix well to obtain a first mixture; 2. The same as step 2 of Example 3, obtain carboxylated polyvinyl chloride sample 2.

[0061] Embodiment 5 In this example, a hydroxylated magnesium aluminum hydrotalcite sample was prepared, and the preparation steps were as follows: 1. According to the mass ratio of ammonium sulfate: serine: pyrophosphoryl chloride: magnesium aluminum hydrotalcite = 4:60:15:100, ammonium persulfate, serine, pyrophosphoryl chloride, and the magnesium aluminum hydrotalcite sample 1 prepared in Example 1 are mixed, and sufficient acetone is used with zirconium dioxide balls as the medium, and wet grinding is performed for 2 hours by a planetary ball mill. After the grinding, the solids are separated to obtain a second mixture; 2. First, mix the ground second mixture with water at a mass ratio of water: second mixture = 10:100, let it stand for 2 hours, then prepare calcium chloride into a 55wt% calcium chloride aqueous solution at a mass ratio of calcium chloride: magnesium aluminum hydrotalcite = 6:100, and according to the addition amount of magnesium aluminum hydrotalcite in the second mixture, add the calcium chloride aqueous solution dropwise to the second mixture and stir evenly, adjust the pH to 10 after the addition is completed, let it stand for 2 hours, separate the solid, wash with water twice, and infrared dry below 100°C to obtain hydroxylated magnesium aluminum hydrotalcite sample 1.

[0062] Embodiment 6 In this example, a hydroxylated magnesium aluminum hydrotalcite sample was prepared, and the preparation steps were as follows: 1. According to the mass ratio of ammonium sulfate: serine: pyrophosphoryl chloride: magnesium aluminum hydrotalcite = 8:80:15:100, ammonium persulfate, serine, pyrophosphoryl chloride, and magnesium aluminum hydrotalcite sample 2 prepared in Example 2 are mixed, and sufficient acetone is used with zirconium dioxide balls as the medium to perform wet grinding for 2 hours by a planetary ball mill. After the grinding, the solids are separated to obtain a second mixture; 2. First, mix the ground second mixture with water at a mass ratio of water: second mixture = 20:100, let it stand for 2 hours, then prepare calcium chloride into a 55wt% calcium chloride aqueous solution at a mass ratio of calcium chloride: magnesium aluminum hydrotalcite = 10:100, and according to the addition amount of magnesium aluminum hydrotalcite in the second mixture, add the calcium chloride aqueous solution dropwise to the second mixture and stir well, adjust the pH to 10 after the addition is completed, let it stand for 2 hours, separate the solids, wash with water twice, and infrared dry below 100°C to obtain hydroxylated magnesium aluminum hydrotalcite sample 2.

[0063] Embodiment 7 In this embodiment, a modified polyvinyl chloride sample is prepared, and the preparation steps are as follows: Concentrated sulfuric acid, hydroxylated magnesium aluminum hydrotalcite sample 1 of Example 5, and carboxylated polyvinyl chloride sample 1 of Example 3 were added to ethanol in a mass ratio of concentrated sulfuric acid: hydroxylated magnesium aluminum hydrotalcite: carboxylated polyvinyl chloride: ethanol = 15:5:100:300, first heated to 50°C, stirred for 1 hour, then subjected to ultrasonic expansion treatment at a frequency of 100 kHz for 2 hours, finally heated to reflux at 80°C for 3 hours, and after the reaction, the solids were separated, washed with acetone twice, washed with water twice, and infrared dried below 100°C to obtain modified polyvinyl chloride sample 1.

[0064] Embodiment 8 In this embodiment, a modified polyvinyl chloride sample is prepared. The preparation steps are the same as those of embodiment 7, except that the hydroxylated magnesium aluminum hydrotalcite used is the hydroxylated magnesium aluminum hydrotalcite sample 2 of embodiment 6, and the carboxylated polyvinyl chloride used is the modified polyvinyl chloride sample 2 of embodiment 4.

[0065] Embodiment 9 This embodiment prepares a polyvinyl chloride insulation material, and the preparation steps are as follows: 1. According to the mass ratio of polyvinyl chloride: polyethylene: ethylene propylene rubber: trimethyl phosphate: dioctyl phthalate: dilauryl thiodipropionate = 65:20:10:2:2:1, the modified polyvinyl chloride sample 1 obtained in Example 7 is used, the above raw materials are fed into a mixer, mixed at 100°C and a speed of 600 r / min for 20 minutes, and extruded and granulated to obtain master batches between 0.5 mm and 1 mm; 2. The mother is sent to a melting device, melted in a temperature range of 185°C to 200°C for 20 minutes, and extruded by a single-screw device to obtain a polyvinyl chloride insulation material sample 1.

[0066] It can be understood that if the extruded material is coated on the surface of the conductor core of industrial pure copper in the above step 2, a photovoltaic cable can be obtained. In order to test the performance of the polyvinyl chloride insulation material in this embodiment, it is directly extruded and then cooled to form.

[0067] Embodiment 10 This embodiment prepares a polyvinyl chloride insulation material, and its preparation steps are the same as those of the ninth embodiment, except that the modified polyvinyl chloride sample 2 obtained in the eighth embodiment is used to obtain the polyvinyl chloride insulation material sample 2.

[0068] Comparative Example 1 This comparative example prepared a polyvinyl chloride insulation material sample 3, and its preparation process is as follows: 1. According to the mass ratio of magnesium-aluminum hydrotalcite: polyvinyl chloride: polyethylene: ethylene-propylene-diene rubber: trimethyl phosphate: dioctyl phthalate: dilauryl thiodipropionate = 3:65:20:10:2:2:1, the magnesium-aluminum hydrotalcite sample 1 of Example 1 and other commercially purchased raw materials are fed into a mixer, mixed at 100° C. and a speed of 600 r / min for 20 min, and extruded and granulated to obtain a masterbatch between 0.5 mm and 1 mm; 2. The mother was sent to a smelting device, melted in a temperature range of 185°C to 200°C for 20 minutes, and extruded by a single-screw device to obtain a polyvinyl chloride insulation material sample 3.

[0069] Comparative Example 2 This comparative example prepared a polyvinyl chloride insulation material sample 4, and its preparation process is as follows: 1. According to the mass ratio of serine to magnesium aluminum hydrotalcite = 60:100, serine and magnesium aluminum hydrotalcite sample 1 prepared in Example 1 are mixed, and sufficient acetone is used with zirconium dioxide balls as the medium to perform wet grinding for 2 hours by a planetary ball mill. After the grinding, the solids are separated to obtain a second mixture; 2. According to the mass ratio of calcium chloride: magnesium aluminum hydrotalcite = 6:100, calcium chloride is prepared into a 55wt% calcium chloride aqueous solution, and according to the addition amount of magnesium aluminum hydrotalcite in the second mixture, the calcium chloride aqueous solution is added dropwise to the second mixture and stirred evenly. After the addition is completed, the pH is adjusted to 10, and after standing for 2 hours, the solid is separated, washed with water twice, and infrared dried at below 100°C to obtain magnesium aluminum hydrotalcite for use in the following steps; 3. Add concentrated sulfuric acid, the magnesium aluminum hydrotalcite obtained in step 2 of this comparative example, and the carboxylated polyvinyl chloride sample 1 of Example 3 to ethanol in a mass ratio of concentrated sulfuric acid: magnesium aluminum hydrotalcite: carboxylated polyvinyl chloride: ethanol = 15:5:100:300, and heat under reflux at 80° C. for 3 h. After the reaction, separate the solid, wash twice with acetone, wash twice with water, and infrared dry below 100° C. to obtain polyvinyl chloride for use in the following steps; 4. According to the mass ratio of polyvinyl chloride: polyethylene: ethylene propylene rubber: trimethyl phosphate: dioctyl phthalate: dilauryl thiodipropionate = 65:20:10:2:2:1, the above raw materials are fed into a mixer, mixed at 100°C and a speed of 600r / min for 20min, and extruded and granulated to obtain masterbatch between 0.5mm and 1mm; 5. The mother is sent to a smelting device, melted in a temperature range of 185°C to 200°C for 20 minutes, and extruded by a single-screw device to obtain a polyvinyl chloride insulation material sample 4.

[0070] Performance Testing The present invention tests the performance of vinyl chloride insulation material samples 1 to 4, and the detection standards of tensile strength and elongation at break refer to GB / T1701-2001. The detection standard of limiting oxygen index refers to GB / T2406.1-2008. The detection standard of thermal conductivity refers to GB / T6344-2008. The conditions of the accelerated aging test are to treat the sample at a temperature of 110°C, a humidity of 80%RH, and 600W 365nm ultraviolet irradiation for 144h. The results of the above performance tests are shown in Table 1.

[0071] Table 1 Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.

Claims

1. A method for preparing a low-smoke halogen-free flame-retardant photovoltaic cable, characterized in that: include: S1, mixing and granulating modified polyvinyl chloride, polyethylene, EPDM rubber and additives to obtain masterbatch; S2, melt-extrude the masterbatch and coat it on the surface of the conductor core to obtain the photovoltaic cable; The surface of the modified polyvinyl chloride is connected with magnesium aluminum hydrotalcite through an esterification reaction.

2. The preparation method according to claim 1, characterized in that: The auxiliary agents include stabilizers, plasticizers and antioxidants; in terms of mass ratio, polyvinyl chloride: polyethylene: EPDM rubber: stabilizer: plasticizer: antioxidant = (60-66): (20-22): (8-12): (2-4): (1-2): (1-2).

3. The preparation method according to claim 2, characterized in that: The stabilizer comprises at least one of the following or a combination thereof: trimethyl phosphate, barium stearate, calcium zinc dimer acid; and / or The plasticizer comprises at least one of the following or a combination thereof: trioctyl trimellitate, tetramethyl pyromellitate, dioctyl phthalate; and / or The antioxidant comprises at least one of the following or a combination thereof: pentaerythritol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and dilauryl thiodipropionate.

4. The preparation method according to claim 1, characterized in that: The mixing temperature of the mixing and granulation is 90° C. to 120° C., the mixing speed is 600 r / min to 1200 r / min, and the mixing time is 15 min to 20 min; and / or The melt extrusion has a melting temperature of 185° C. to 200° C. and a melting time of 20 min to 40 min.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The modified polyvinyl chloride is prepared by the following steps: A1. Treating polyvinyl chloride with glutathione to obtain carboxylated polyvinyl chloride; A2, treating the hydrotalcite with serine to obtain hydroxylated magnesium aluminum hydrotalcite; A3. Mixing and heating the hydroxylated magnesium aluminum hydrotalcite and the carboxylated polyvinyl chloride under acidic conditions to obtain the modified polyvinyl chloride.

6. The preparation method according to claim 5, characterized in that: The hydroxylated magnesium aluminum hydrotalcite is subjected to chemical expansion intercalation treatment using ammonium sulfate and serine as intercalation agents, and ultrasonic expansion intercalation treatment.

7. The preparation method according to any one of claims 1 to 4, characterized in that: The modified polyvinyl chloride is prepared by the following steps: B1. Dissolve glutathione in water, add triethanolamine, polyvinyl alcohol, polyvinyl chloride and ethanol, heat and reflux to obtain carboxylated polyvinyl chloride; B2, after ammonium persulfate, serine, pyrophosphoryl chloride and magnesium aluminum hydrotalcite are uniformly mixed, water is added for chemical expansion and intercalation treatment, and then calcium chloride aqueous solution is added dropwise and alkalization treatment is performed to obtain hydroxylated magnesium aluminum hydrotalcite; B3, adding concentrated sulfuric acid, the hydroxylated magnesium aluminum hydrotalcite and the carboxylated polyvinyl chloride into ethanol, heating and applying ultrasound to perform ultrasonic expansion and intercalation treatment, and then heating and refluxing to obtain the modified polyvinyl chloride.

8. The preparation method according to claim 7, characterized in that: In B1, by mass ratio, triethanolamine:polyvinyl alcohol:glutathione:polyvinyl chloride:water:ethanol=(2-4):(4-6):(6-8):(20-30):(10-15):100; and / or In B2, by mass ratio, calcium chloride: ammonium sulfate: serine: pyrophosphoryl chloride: magnesium aluminum hydrotalcite = (6-10): (4-8): (60-80): (10-20): 100; and / or In B3, the mass ratio is: concentrated sulfuric acid: hydroxylated magnesium aluminum hydrotalcite: carboxylated polyvinyl chloride: ethanol = (15-20): (4-6): 100:

300.

9. The preparation method according to claim 7, characterized in that: In B1, the heating reflux reaction temperature is 80° C. to 90° C., and the time is 8 h to 12 h; and / or In B2, the magnesium aluminum hydrotalcite is prepared by a chemical method in an alkaline environment using magnesium salt and aluminum salt as raw materials; and / or In B3, the frequency of the ultrasonic expansion treatment is 80kHz to 120kHz, and the time is 2h to 3h; and / or In B3, the heating reflux reaction temperature is 80° C. to 90° C., and the time is 2 h to 4 h.

10. A low-smoke, halogen-free, flame-retardant photovoltaic cable, characterized in that: The low-smoke halogen-free flame-retardant photovoltaic cable is obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Fibres of polyvinyl chloride reticulated with diisocyanates and process for their preparation

    EP0488907A1

  • Silane crosslinked polyvinyl chloride resin and method for producing molding thereof

    JP2018083937A

  • Nucleophilic substitution of chlorine containing polymers in aqueous medium by amido-thiolate groups

    US4735997A

Cited By

  • Flame-retardant modified PVC plastic sheet and preparation method thereof

    CN120173347A